CTNI-79. PRICOTTF TRIAL: A PHASE I/II TRIAL OF TTFIELDS PRIOR AND CONCOMITANT TO RADIOTHERAPY IN NEWLY DIAGNOSED GLIOBLASTOMA. (9th November 2020) - Kebir, Sied; Lazaridis, Lazaros; Schmidt, Teresa; Oster, Christoph; Pierscianek, Daniela; Guberina, Nika; Kleinschnitz, Christoph; Proescholdt, Martin; Hau, Peter; Grosu, Anca-Ligia; Sure, Ulrich; Scheffler, Björn; et al.
Abstract: OBJECTIVE: Survival rates were significantly improved when adding TTFields to adjuvant chemotherapy with temozolomide in patients with newly diagnosed glioblastoma (nGBM) in the phase 3 EF-14 trial. TTFields therapy is applied at 200 kHz by arrays that are placed at the patients' scalp. In preclinical studies, the combination of TTFields and radiotherapy demonstrated synergistically enhanced efficacy in GBM cells. Here, we present the PriCoTTF trial, which is currently enrolling nGBM patients and will assess the safety and efficacy of TTFields initiated prior and concomitant to radiochemotherapy. METHODS: After surgery and complete wound-healing, TTFields therapy will be initiated in newly diagnosed GBM patients. TTFields therapy will continue throughout radiochemotherapy and adjuvant chemotherapy for a total of approximately 9 months. Radiotherapy will be conducted through the arrays, by which TTFields therapy is delivered. Totally, thirty-three patients will be enrolled in two arms. In arm A, 20 adult patients will be enrolled to receive normo-fractionated radiotherapy and in arm B, 13 elderly patients will be treated by hypo-fractionated radiotherapy. The patients will receive chemotherapy according to institutional standard and interdisciplinary tumor conference. RESULTS: Safety and tolerance based on the frequency of pre-specified treatment-limiting toxicities is defined as primary endpoint of the trial. Secondary endpoints include the frequency of adverse events, progression-free survival (PFS), and overall survival (OS). The trial is currently enrolling patients at four sites in Germany. To date, 13 patients were included (May 2020). Initial practical experiences will be presented. CONCLUSION: The combination of TTFields and radiotherapy is an encouraging approach to further improve survival of GBM patients. In the presented phase I/II trial, the safety and efficacy of TTFields initiated prior and concomitant to RT in newly diagnosed GBM will be assessed. In addition, initial efficacy data (phase II) can serve as a rationale for a randomized phase III trial.